KONSTRUKSI MEDIA, MULTIKULTURALISME, DAN EKSISTENSI UNDANG -UNDANG PENYIARAN DI INDONESIA - Agus Maladi Irianto (Masalah-Masalah Hukum, 2011)
Media has developed not only to represent knowledge, idea and point of view which then it develops a solid structure as well as in the stable society where there is no conflict of interest. The recent media has build a social reality from an industry that is presented to a community which is dynamic, contemporer and constantly changing. The sibbholeth of "Bhineka Tunggal lka· today is no longer about the ethnic and the cultural diversity but it is about the cultural diversity that exists in Indonesian society. The main reference for the establishment of Indonesia's multicultural society is multiculturalism, an ideology that recognizes and exalts the difference in the equality of both individually and culturally. The presence of media - in line with the multiculturalism spirit - should be the adhesive of some separate identities (importances). It has to be admitted that the national integration, which is constructed by the media (especially by television) has created the interest uniformity that no longer relevant with the spirit of global democracy and multiculturalirm. The condition occured because the Broadcasting Act (UU Penyiaran No. 3212002) that control the presence of the television industry in Indonesia is not functioning properly and it is violated by the Indonesian television worker. The Broadcasting Act is not functioning properly because the authority holder of the broadcasting act in Indonesia is in weak position.